Reducing Hunger Among Women and Children in India. Issue 4 (July 2018) - Callister, Lynn Clark
Abstract : There are approximately 195 million undernourished people living in India, which constitutes 25% of the global hunger burden. Our global health nursing expert, Dr. Callister, provides an update on the health and nutrition situation in India and current efforts for improvement.